2018
DOI: 10.3892/ijmm.2018.3481
|View full text |Cite
|
Sign up to set email alerts
|

Iron limitation promotes the atrophy of skeletal myocytes, whereas iron supplementation prevents this process in the hypoxic conditions

Abstract: There is clinical evidence that patients with heart failure and concomitant iron deficiency have increased skeletal muscle fatigability and impaired exercise tolerance. It was expected that a skeletal muscle cell line subjected to different degrees of iron availability and/or concomitant hypoxia would demonstrate changes in cell morphology and in the expression of atrophy markers. L6G8C5 rat skeletal myocytes were cultured in normoxia or hypoxia at optimal, reduced or increased iron concentrations. Experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The intracellular iron content was assessed by means of flame atomic absorption spectroscopy assay [ 14 ], as described in detail in our previous work [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intracellular iron content was assessed by means of flame atomic absorption spectroscopy assay [ 14 ], as described in detail in our previous work [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…As ~10% of total body iron is stored in skeletal muscle, the impact of iron overload on muscle phenotype has also been explored during the last decade 18 . Previous studies reported a strong correlation between muscle iron accumulation occurring with ageing, ROS production, and muscle wasting 19–22 . Moreover, iron overload‐induced skeletal muscle atrophy has been associated with ROS‐mediated ubiquitin–proteasome system activation 22–24 .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Moreover, iron overload-induced skeletal muscle atrophy has been associated with ROS-mediated ubiquitin-proteasome system activation. [22][23][24] However, the iron supplementation used in these studies causes systemic and cellular iron overload, [22][23][24] much higher than that observed under pathophysiological conditions, especially in patients with haemochromatosis. 25 Although extra-physiological iron overload is known to induce skeletal muscle wasting, the impacts of iron excess close to pathophysiology levels on skeletal muscle mass and cellular mechanisms involved in iron homeostasis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 4 days of hypoxia (10% O 2 ), iron chelation in rats decreased RV hypertrophy and GATA4 expression, which plays a major role in its adaptation to pressure overload [ 89 , 90 ]. In fact, iron deficiency promoted skeletal muscle atrophy, while iron supplementation had the opposite effect, suggesting that iron is required for muscle adaptation to overload [ 91 ]. Myoglobin, which serves as a skeletal muscle iron store, plays an important role in the adaptation of the RV to pressure overload [ 92 ].…”
Section: Iron Status In Pah and Experimental Phmentioning
confidence: 99%